Academic Community and Policymaking in Russia: Impact or Detachment?. Issue 4 (4th July 2019) - Kaczmarska, Katarzyna
Abstract : This paper is concerned with the role of International Relations (IR) expertise and the academia–policy nexus in contemporary Russia. Drawing on interviews with Russia-based scholars, it posits that while there exist formal channels of knowledge diffusion between academia and the state, there is no clear-cut relationship between knowledge produced in academia and the uses of this knowledge by the state. Scholars' attitudes towards policy impact, while generally skeptical, span a broad spectrum. Some are convinced that achieving impact is impossible, some declare unwillingness to interact with the policymaking world, while others find providing expert advice difficult but possible under certain conditions.